The Effect of Green Tea on Blood Pressure Reduction among Hypertension Patients - Adwiyah; Mukhtar; Siregar, Sarmaida; Dewi, Ratna (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Blood pressure is an important indicator of the circulatory system. An increase or decrease in blood pressure will affect the balance in the body. Hypertension is a condition when the systolic blood pressure is more than 140 mmHg and the diastolic pressure is more than 90 mmHg. High blood pressure is also called the silent killer because it is a deadly disease. Green tea (Camellia Synesis) contains polyphenols, these compounds can reduce the risk of cardiovascular diseases such as blood cholesterol levels and blood pressure. Objective: This study aims to analyze the difference in blood pressure before and after giving green tea to hypertensive patients at the Imelda Hospital in Medan. Method: The research method used in this study is the Quasi-Experiment method with a research design using pre-test and post-test one group design. The population of this study was 295 patients or respondents and the sample in this study were 33 patients or respondents. Data were analyzed by Univariate and Bivariate using Wilcoxon test. Result: The results showed that the effect of giving green tea on blood pressure was p-value = 0.000 <0.05, which means that there was an effect of giving green tea on blood pressure at Imelda Hospital Medan. Recommendation: It is hoped that this research will serve as information for the public to know about the benefits of giving green tea to lowering blood pressure as an alternative to non-pharmacological therapy so that blood pressure remains normal and stable